System development methodology for interactive information system development - Lee, Hee Wee; Overby, Magnus B.; Sadananda, Ramakoti; Duangkaew Sawamiphakdi; DAAD (Bangkok : Asian Institute of Technology, 1985)
A system development methodology is proposed here which could help to boost productivity of the development process. This methodology is designed to interface with the 4th Generation Software Development tool. The development process is also changed to adopt the prototyping approach in implementation. The approach to analysis is by performing an through study of the user's interaction with the system by combining both the data-flow and functional analysis. The user's views of the system is then integrated to form a community view which is then used as a basis for data modeling for the enterprise underlying database. The methodology is applied in developing a Manpower System for the Thai Association of Overseas Placement Agencies. Productivity gained is measured as compared to developing it using the traditional methodology
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1985
Keywords: Interactive computer systems